From 5G to 6G : technologies, architecture, AI, and security - Yarali, Abdulrahman (Hoboken, New Jersey : Wiley, 2023)
"The transition from the fifth generation of wireless communication (5G) to the coming sixth generation (6G) promises to be one of the most significant phases in the history of telecommunications. The technological, social, and logistical challenges promise to be significant, and meeting these challenges will determine the future of wireless communication. Experts and professionals across dozens of fields and industries are beginning to reckon seriously with these challenges as the 6G revolution approaches. From 5G to 6G provides an overview of this transition, offering a snapshot of a moment in which 5G is establishing itself and 6G draws ever nearer. It focuses on recent advances in wireless technology that bring 6G closer to reality, as well as the near-term challenges that still have to be met for this transition to succeed. The result is an essential book for anyone wishing to understand the future of wireless telecommunications in an increasingly connected world."--
Includes index.
Keywords: Mobile communication systems -- Technological innovations; Mobile communication systems -- Security measures; Artificial intelligence; Print books